Qui sont les « élus de l’eau » ? À propos de l’investissement sectoriel des élus locaux - Sylvain Barone; Bastien Sannier; Maylis Razès; Myriam Campardon; Laetitia Guérin-Schneider; Audrey Richard-Ferroudji (Développement Durable et Territoires)
This article intends to better understand who are the "water representatives" in France, defined here as the (local) elected officials with responsibilities in managing water bodies and aquatic environments. Is their involvement in this area based on a specific skill or interest? Is water on the contrary a sector like the others, where individual trajectories rest on classical logics of social and political selection? Based on two quantitative surveys, this article draws a portrait of "water representatives". It analyzes their mandates and functions, their sociological and political profiles, their relationship to water, before placing their sectoral involvement in the wider range of their political.